Meningkatkan Kinerja Karyawan BPJS Ketenagakerjaan Cabang Jakarta Gambir: Analisis Peran Budaya Organisasi dan Lingkungan Kerja dengan Mediasi Public Service Motivation - Asep Sansan; Sri Astuti Pratminingsih (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to empirically examine the influence of Organizational Culture and Work Environment on Employee Performance at BPJS Ketenagakerjaan Jakarta Gambir Branch, with Public Service Motivation (PSM) as an intervening variable. The research is grounded in the growing demand for high-quality public services, which requires optimal employee performance aligned with public service values. A quantitative approach with an explanatory research design was employed to analyze causal relationships among variables. Data were collected through structured questionnaires distributed to 30 employees using a saturated sampling technique, ensuring that all members of the population participated as respondents. Structural Equation Modeling–Partial Least Square (SEM-PLS) was utilized to assess measurement validity, reliability, and structural relationships among constructs. The findings reveal that Organizational Culture and Work Environment have a positive and significant effect on Employee Performance, both directly and indirectly through PSM. PSM functions as a partial mediation variable, strengthening the relationship between Organizational Culture, Work Environment, and Employee Performance. These results indicate that stronger organizational values and a more conducive work environment enhance employees’ public service motivation, ultimately improving their performance outcomes. The novelty of this research lies in examining the mediating role of PSM within the institutional context of BPJS Ketenagakerjaan, which remains underexplored in Indonesian public sector management studies.